A Lagrangian Description of Buoyancy Effects on Aircraft Wake Vortices from Wing Tips near a Heated Ground Plane - Moraes, Paulo Guimarães de; Oliveira, Marcos André de; Bimbato, Alex Mendonça [UNESP]; Pereira, Luiz Antonio Alcântara (MDPI, 2022)
The present paper introduces the key ideas of a purely Lagrangian temperature particle method, which includes preheating effects on fluid flow nearest a heated wall. The numerical approach is then applied for the study of mixed heat transfer on aircraft wake vortices from wing tips in the vicinity of a heated ground plane, a situation commonly found during landing or takeoff operations at airports around the world. It was found in the literature experimental results of an investigation without the effects of heat transfer and crosswind, which were useful for a comparison with some present numerical results. Other numerical results are also discussed, focusing on the physics of the effects of mixed convection heat transfer and crosswind. As a contribution, the Richardson number is defined in terms of both aircraft wingspan and constant ground plane temperature, being the most important dimensionless group to capture the effects of laminar ascending mixed convection flow. The present methodology presents potentialities for predicting the transport and decay of primary vortical structures (under buoyancy forces), including their interaction with secondary vortical structures generated from a ground plane.
Keywords: aircraft wake; buoyancy forces; crosswind; numerical simulation using parallel processing; preheating effects; vortex and temperature particles